The Differentiation Of Marketing Strategies To Increase Sales Volume CGV Kediri Mall - Pamungkas, Bimantara Diaz; Subagyo, Subagyo (Universitas Nusantara PGRI Kediri, 2024)
Research aim: This research aims to identify and analyze differentiation in marketing strategies at CGV Kediri Mall. Design/Method/Approach: Using qualitative descriptive research methods, data was collected through interviews, observation, and analysis of research-related documents. In this research, the data source comes from the marketing strategy differentiation process while the research object is CGV Kediri Mall. Research Findings: The findings in this research reveal how differentiation elements, especially product and customer service, in marketing strategies can increase sales of CGV Kediri Mall. Theoretical contribution/Originality: This research contributes theoretically by aligning the findings with relevant marketing theories and models, providing insight into the effectiveness of differentiation strategies. Practitionel/Policy implications :Practical implications include recommendations for optimizing differentiation strategies, enhancing brand image, and gaining competitive advantage. Research limitations:The main focus of research is product and service differentiation in increasing sales.